Role of CA 19-9/CRP Ratio as A Predictor for Malignancy in Obstructed Jaundice Patient: CA 19-9/CRP Ratio for Malignancy in Obstructed Jaundice Patient - Anwar, Ayesha; Khanum, Rabia; Faridi, Maarij; Akram, Waseem; Mahmood, Misbah (Pakistan Journal of Health Sciences, 2024)
The cancer-antigen-19-9 tumor marker, increases during biliary and pancreatic malignancy. Objectives: To determine diagnostic accuracy and role of cancer-antigen-19-9 and C-reactive-protein ratio as a predictor for malignancy in obstructive jaundice patients taking a Computed Tomography scan as the gold standard. Methods: A total of 158 patients were admitted with obstructive jaundice in Al-Tibri Hospital. Cancer-antigen-19-9 was adjusted by dividing it with the C-reactive-protein value. Malignancy was considered based on computed tomography scan findings. Specificity, sensitivity, negative predictive value, positive predictive value, and diagnostic accuracy of cancer antigen-19-9 to C-reactive protein ratio were calculated. Results: There were 57.6% male and 42.4% female patients. The mean cancer antigen-19-9 and C-reactive-protein ratio was 51.39 ± 69.40 U/ml. The significant p-values (<0.001) confirm meaningful differences in CA19-9/CRP ratios between benign and malignant cases, but low sensitivity (63.2%) and negative predictive value (46.8%) limit its clinical utility as a standalone tool. A total of 50% of patients were diagnosed as benign and 50% as malignant by cancer antigen-19-9 and C-reactive-protein ratio. However, 27.8% of patients were diagnosed as benign and 72.2% as malignant by computed tomography scan. Sensitivity, Specificity, positive predictive value, negative predictive value and accuracy were 63.2%, 84.1%, 91.1%, 46.8%, and 68.98% respectively. Conclusions: It was concluded that the cancer-antigen-19-9/CRP ratio while exhibiting moderate overall diagnostic accuracy (68.98%), provides significant diagnostic specificity (84.1%) and positive predictive value (91.1%). These characteristics make it a valuable supplemental tool for confirming malignancy in obstructive jaundice patients, particularly when used alongside other diagnostic modalities.